Teologi Ekologi Sebagai Kerangka Teologis Gereja Dalam Merespons Krisis Lingkungan di Indonesia: Sebuah Analisis Literatur - Fatony Pranoto (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
Indonesia’s environmental crisis demands a church response that is not merely practical but grounded in systematic and contextual theological reflection. Although many churches have demonstrated concern for environmental issues, such responses often remain fragmented and insufficiently integrated into a coherent ecological theological framework. This article aims to analyze the urgency of developing ecological theology as a theological foundation for Indonesian churches in addressing environmental crises sustainably.This study employs a qualitative theological literature analysis through critical dialogue with the paradigms of missio Dei, ecological justice within liberation theology, and integral ecotheology. The analysis focuses on Indonesia’s environmental crisis, ecclesial practices, and the challenges and opportunities for developing ecological theology in the Indonesian church context. The findings indicate that ecclesial responses have not yet been fully supported by systematic theological reflection, limiting their long-term transformative impact. This article contributes a contextual ecological theological framework that bridges theological reflection and ecclesial praxis in Indonesia, emphasizing the integration of faith, social justice, and ecological responsibility as an essential dimension of the church’s mission.